If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(9n + 4) = 22 + -7n Reorder the terms: -2(4 + 9n) = 22 + -7n (4 * -2 + 9n * -2) = 22 + -7n (-8 + -18n) = 22 + -7n Solving -8 + -18n = 22 + -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. -8 + -18n + 7n = 22 + -7n + 7n Combine like terms: -18n + 7n = -11n -8 + -11n = 22 + -7n + 7n Combine like terms: -7n + 7n = 0 -8 + -11n = 22 + 0 -8 + -11n = 22 Add '8' to each side of the equation. -8 + 8 + -11n = 22 + 8 Combine like terms: -8 + 8 = 0 0 + -11n = 22 + 8 -11n = 22 + 8 Combine like terms: 22 + 8 = 30 -11n = 30 Divide each side by '-11'. n = -2.727272727 Simplifying n = -2.727272727
| h^2-3h+c=0 | | 4m^2+2n=3 | | 6x+8-13x+10=x+6+x+3x | | -5g=g-h | | 2(3c-1)-4=4c+8 | | (3d+6)(4d-11)=0 | | 10x+3x-4= | | 12x-3x+6x+5x= | | 2x(x+5)=870 | | 5y=4y^2-6 | | 2x^2-20x-44=0 | | 6c^2-11c+3=0 | | x^5-789=0 | | 2x+3x-3+10=4x+14 | | 6x+6=-112-10x | | 12x^4+12x^3-9x^2+16x-4=0 | | 27=0.428x | | 7x+3x-4x+11=7x+17-4x | | 6x^2=2x+2 | | 6(3x+3)=-198 | | -10=0.8y+6 | | -5x+4=-3x-2 | | 6x-3+2x=-67 | | 6x-3+2x=-64 | | 4(6x+2)=-112 | | -6x+1=5x+45 | | -23=3x+x+1 | | -7x-8=-1 | | 6(2x-1)=8x-2 | | 9x+5=4x+50 | | -x+9=-6+2x | | 0.85x+3y=0 |